A secondary, coplanar design Ni/MCM-41/Zn microbattery - Meskon, Shahrul Razi; Othman, Raihan; Ani, Mohd Hanafi (Institute of Physics Publishing, 2018)
A secondary Ni/Zn microbattery (200 µm thick) has been developed in a coplanar electrode configuration. The cell is essentially of a circular shape (30 mm in diameter) consisting of a fine circular ring (cathode) and a circle (anode) split apart (~800 µm). Unlike the stacking cell architecture, coplanar configuration offers simple design, ease of fabrication and eventually cost saving. The use of MCM-41 mesoporous silica as the membrane separator cum electrolyte reservoir enables the successful implementation of coplanar configuration. The fabrication of Ni/Zn microbattery first begins with electrodeposition of zinc (Zn) and nickel hydroxide (Ni(OH)2) thin films onto patterned FR4 printed circuit board, followed by deposition of zinc oxide (ZnO) slurry onto the zinc active layer, and finally ends by multiple drop-coating procedures of MCM-41 from its precursor solution at ambient temperature. Once a potassium hydroxide (6 M KOH)/MCM-41 electrolyte-separator mixture is incorporated, the cell is sealed with an acrylic sheet and epoxy adhesive. The fabricated microbatteries were capable to sustain around 130 deep charge-discharge cycles. When rated at 0.1 mA, the energy density of the microbattery was around 3.82 Wh l-1 which is suitable for low rate applications and storage for micro energy harvesters such as piezoelectric generators.